Impact of the European Central Bank Monetary Policy on the Financial Indicators of the Bulgaria, Croatia, Romania and Ukraine: Array - Alekseievska , Halyna (Acta Universitatis Danubius. Œconomica, 2020)
The recent financial crisis has forced the central banks of many countries to use new monetary policy methods. The purpose of this research is to study the impact of the ECB's unconventional monetary policy on the Central and Eastern European countries, as they have economic and trade relations with the euro area. The influence of the ECB policy on the yield of long-term government bonds Bulgaria, Romania, Croatia and Ukraine and the investment flows in these countries were studied using VAR models. Unconventional monetary policy measures were presented by the volume of ECB’s assets balance sheet. The quarterly data was taken from the International Monetary Fund and Organization for Economic Co-operation and Development. As a result, was revealed a significant influence of the ECB's long-term interest rate on the yield government bonds of the studied countries. Also, the ECB policy stimulated the flow of investments, mainly in debt securities of Croatia, Romania, and Ukraine, with a predominance of portfolio investments.